PERAN ACADEMIC SELF-EFFICACY DAN PEER SUPPORT TERHADAP ACADEMIC BURNOUT MAHASISWA PENULIS SKRIPSI - Chandana Devi, Audrey; Purwanti, Margaretha; Aisyah, Aireen Rhammy Kinara (MANASA, 2024)
Completing a thesis is a major academic milestone but often leads to fatigue, stress, and academic burnout. This study examined the roles of academic self-efficacy (an internal factor) and peer support (an external factor) in academic burnout among 7th-semester psychology students completing a 3.5-year thesis at Atma Jaya Catholic University of Indonesia. The study used a quantitative predictive design with 61 participants from the 2020 cohort. Data were collected using the Maslach Burnout Inventory–Student Survey (MBI-SS), The Academic Self-efficacy Scale, and the Peer Support Scale. Multiple linear regression analysis was conducted to assess the relationships among the variables. Results indicated that academic self-efficacy and peer support together significantly influenced academic burnout. Academic self-efficacy showed a significant negative contribution, while peer support had a negative but nonsignificant effect. Burnout levels among participants ranged from moderate to low, while academic self-efficacy and peer support levels were high. Future research could explore the relationship between 3.5-year thesis completion and positive psychological variables related to academic achievement at the Faculty of Psychology, Atma Jaya Catholic University of Indonesia.